Self Expressiveness, Brand Trust, Hedonic Product, Brand Community, Word of Mouth, dan Brand Experience Terhadap Brand Love pada Merek Vespa - Herdiany, Hapsari Dyah; Basri, Anindita Imam; Utomo, Chandra Wisnu; Pramudya, Krisna (Efektor, 2024)
Self-expressiveness, brand trust, hedonic product, brand community, word of mouth, and brand experience regarding brand love for Vespa brand motorbikes are the titles of this research. The population is someone who has used, purchased and used Vespa products in Indonesia. The sample in this study amounted to 260 respondents using non-probability sampling. The research method uses a quantitative approach and data analysis uses multiple linear regression. The results of the t-test showed that the significance value of the four independent variables was <0.05; all independent variables partially had a positive effect on the dependent variable. The F test shows that self-expressiveness, brand trust, hedonic product, brand community, word of mouth, and brand experience on brand love have a simultaneous influence with a calculated F value of 31,436 with a significance of 0.000 (<0.5).